Education policy and the heritability of educational attainment - A.C. Heath; K. Berg; L.J. Eaves; M.H. Solaas; L.A. Corey; J. Sundet; P. Magnus; W.E. Nance (Norsk Forening for Epidemiologi, 2016)
Is not included in the online volume due to copyright (Nature 1985; 314: 734-736, reprinted in the paper edition with permission from the Nature Publishing Group)